2014
DOI: 10.1111/cei.12381
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like receptor expression in crypt epithelial cells, putative stem cells and intestinal myofibroblasts isolated from controls and patients with inflammatory bowel disease

Abstract: The aim of our studies was to investigate the expression of Toll-like receptor (TLR)-2 and TLR-4 (and in some studies TLR-5) in myofibroblasts and small and large intestinal crypt epithelial cells from control patients and those affected by Crohn’s disease and ulcerative colitis. Isolated and disaggregated crypt epithelial cells and monolayers of myofibroblasts were used for studies by reverse transcription–polymerase chain reaction (RT–PCR), real-time RT–PCR, flow cytometry, immunocytochemistry and Western bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 44 publications
1
35
0
Order By: Relevance
“…TLRs recognize the harmful compounds in the extracellular domain and subsequently transduce signals through downstream molecule MyD88 to stimulate innate immune responses against damages and infections, thus paving way for successful adaptive immunity [39]. Studies in mice have demonstrated that TLR-2, TLR-4, and TLR-5 regulate intestinal epithelial homeostasis and provide protection from injury, such as that mediated by IND, radiation, and dextran sodium sulphate [40]. In this study, we examined levels of TLR-2 and MyD88 mRNA and protein expression in the duodenal mucosa lesions to investigate whether innate immunity had some association with the treatment and prevention of duodenal ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…TLRs recognize the harmful compounds in the extracellular domain and subsequently transduce signals through downstream molecule MyD88 to stimulate innate immune responses against damages and infections, thus paving way for successful adaptive immunity [39]. Studies in mice have demonstrated that TLR-2, TLR-4, and TLR-5 regulate intestinal epithelial homeostasis and provide protection from injury, such as that mediated by IND, radiation, and dextran sodium sulphate [40]. In this study, we examined levels of TLR-2 and MyD88 mRNA and protein expression in the duodenal mucosa lesions to investigate whether innate immunity had some association with the treatment and prevention of duodenal ulcer.…”
Section: Discussionmentioning
confidence: 99%
“…Increased expression of TLR4 has been reported in the mucosa of patients with IBD and IBS . Similarly, the expression of TLR2 has been reported to be increased in IBD or remained unchanged in IBD or IBS . However, the role of TLRs in the regulation of intestinal motility is still widely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…84 Compared with control cells, we have recently reported enhanced expression of TLR2 and TLR4 in crypt epithelial cells isolated from colonic mucosal samples affected by active ulcerative colitis and Crohn's disease. 85 Putative crypt epithelial stem cells also expressed TLR2, TLR4, and TLR5, which may mediate protection against CDI.…”
Section: Innate Immune Responsesmentioning
confidence: 99%